Low-impact aerobic exercise as a non-pharmacological intervention for reducing uric acid levels - Wachidah Yuniartika; Agus Sudaryanto; Nieldya Nofandrilla; Dyaz Surya Ananta; Zuan Nun Alea; Aisyiyah Dani Hanifah (Community Empowerment, 2024)
Decreased physical activity in the elderly can lead to an increase in uric acid levels. There is no cure for rheumatoid arthritis, therefore, the treatment provided can only minimize the impact of the disease and optimize health. Low impact aerobic exercise is a type of physical activity suitable for the elderly. This exercise has a low intensity and does not put pressure on the joints, making it safe for the elderly. The purpose of this community service is to reduce uric acid levels with low impact aerobic exercise as a non-pharmacological therapy in the community. This activity was carried out in the form of uric acid checks, health education about uric acid, and low impact aerobic exercise practice. Furthermore, the elderly were asked to undergo therapy at home for 4 weeks with 2 exercise sessions per week with a duration of 45 minutes each session, using a booklet guide. This activity showed success as evidenced by a decrease in uric acid levels. In addition, the results of interviews with the elderly also revealed that they rarely experienced joint pain and looked more cheerful.